A new Characterization of some distributions Based on the r th conditional moment of doubly truncated mean function (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
New characterizations of doubly truncated exponential and geometric distributions are presented by using the s th conditional expectation in terms of their failure rate and reversed failure rate. These results may serve as generalization of several other results in the literature. This characterization generalizes a result of Nofal (2010).